Response of photomorphogenic tomato mutants to nutrient omissions - Barreto, Rafael Ferreira [UNESP]; dos Santos, Luiz Cláudio Nascimento [UNESP]; de Mello Prado, Renato [UNESP]; Campos, Cid Naudi Silva; da Silva Júnior, Gabriel Barbosa; Barreto, Cláudio Ferreira [UNESP]; Teodoro, Paulo Eduardo; Carvalho, Rogério Falleiros [UNESP] (Springer Nature, 2021)
Light is a critical environmental factor that influences nutrient uptake, but understanding how light acts on nutrient uptake is still very elusive. To verify the role of opposite light responses in accumulation, nutrient use efficiency (UE) and growth, a tomato cultivar Micro-Tom (MT), the non-mutant high-pigment-1 (hp1, light exaggerated response) and the mutant aurea (au, phytochrome-deficient) were grown under hydroponic conditions with a complete nutrient solution (CS) or with the individual omission (–) of N, P, K, Ca and Mg. Our results showed that in -N, hp1 exhibited high NUE in the roots and increased root dry mass. In -P, MT compensated the lower accumulation of this nutrient with the increase in PUE and produced shoot dry mass equivalent to the other genotypes with higher PUE and less PUE. In -K, the higher shoot KUE of the au was evidenced by the higher shoot dry weight in relation to the MT. In -Ca, the shoot dry weight loss of hp1 was lower in relation to the other genotypes. In -Mg, hp1 had a low shoot and root MgUE. Finally, we highlighted the perspective of utilizing hp1 in breeding programs as a tool to stimulate root growth under N deprivation conditions, hp1 for poor Ca environments, and au for poor K environments.
Keywords: Abiotic stress; aurea mutant; high-pigment-1 mutant; Solanum lycopersicum L